Delayed Recognition: A Co-Citation Perspective - Zhao, Wenxi; Korobskiy, Dmitriy; Chacko, George (Frontiers in Research Metrics and Analytics, 2021)
A Sleeping Beauty is a publication that is apparently unrecognized by citation for some period of time before experiencing a burst of recognition. Various reasons, including resistance to new ideas, have been attributed to such delayed recognition. We study this phenomenon in the special case of co-citations, which represent new ideas generated through the combination of existing ones. Using relatively stringent selection criteria derived from the work of others, we analyze a very large dataset of over 940 million unique co-cited article pairs, and identify 1,196 cases of delayed co-citations. We further classify these 1,196 cases with respect to amplitude, rate of citation, and disciplinary origin.